A longitudinal study of e-government maturity - Das, A; Singh, H; Joseph, D (Queensland University of Technology, 2011)
Extending the findings of prior cross-sectional studies, this paper presents a longitudinal analysis of the drivers of e-Government maturity. We constructed a panel dataset for the period from 2003 to 2007 using data published by various authoritative sources. We fitted a mixed-effects regression model to the data to study how the growth of e-Government around the globe is influenced by changing levels of affluence, ICT infrastructure, human capital, and governance. We found that countries’ e-Government matures as they become more affluent (in terms of GDP per capita) and as their ICT infrastructure improves. Human capital and the quality of governance have no significant effect on the development of e-Government maturity. The results suggest that countries investing in leading-edge ICT infrastructure can maintain or improve their global standing in e-Government without substantial changes to human capital or governance. We put forward plausible reasons to explain our findings, and their implications for future research and the practice of e-government.
Keywords: e-Government maturity; ICT infrastructure; human capital index; random effects models; panel data analysis; longitudinal analysis; governance